Realistic Mathematic Education: a theoretical- methodological approach to the teaching of mathematics in countryside schools - Marcos Guilherme Moura-Silva; Rayza de Oliveira Souza; Tadeu Oliver Gonçalves; Ruy Guilherme Braga Borges (Universidade Federal do Norte do Tocantins, 2020)
The movement for a Rural Education still lacks investigations of methodological theoretical assumptions for the didactic field, based on the study of teaching practices that consider the object of knowledge and, at the same time, value the realistic/contextual aspect in which the student is inserted. From this perspective, we investigate the methodological theoretical implications of the theory of Realistic Mathematical Education (EMR) for the teaching of mathematics in the countryside school. Based on a qualitative methodological approach, a hypothetical learning path was elaborated based on the principles of EMR related to the teaching of analytical geometry, from the practice of soil modeling in passion fruit (passiflora edulis) cultivation. Our results point to the EMR as a promising methodological theoretical approach of didactic exploration to the countryside context capable of promoting formal reasoning, concepts in realistic situations, appropriation of mathematical language and potential for the development of concepts in the field of Cartesian geometry.